The effectiveness of high-frequency monopolar diathermocoagulation in the treatment of chronic pulpitis - F. Yu. Daurova; A. G. Volkov; N. Zh. Dikopova; D. I. Tomaeva; A. V. Arzukanyan (LLC "Endo Press", 2020)
Aim. A study of the animicrobial action and clinical efficacy of high-frequency monopolar diathermocoagulation in the treatment of chronic forms of pulpitis. The reason for the development of complications in endodontic treatment is poor-quality instrumental treatment root canals.Materials and methods. 102 patients with various chronic forms of pulpitis were divided into three groups of 34 patients each. In the first two groups, high-frequency monopolar diathermocoagulation was used in endodontic treatment in different modes. In the third group, endodontic treatment was carried out without the use of diathermocoagulation (comparison group). The root canal microflora in chronic pulpitis in vivo was studied twice-before and after diathermocoagulation.Results. It was established that high-frequency monopolar diathermocoagulation in the effect mode is 3, power is 4 (4.1 W) and effect is 4, power is 4 (5.4 W) with an exposure time of 3 seconds, it has a pronounced antibacterial effect on all presented pathogenic microflora obtained from the root canals of the teeth. High clinical efficacy of high-frequency monopolar diathermocoagulation in the treatment of teeth with chronic pulpitis has been proved.